Kaedah-Kaedah Ushul Pengertian dan Jenis Nya - Madina, Siti; F, Fatmawati; Sunusi, Muh. Nur Taufiq (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Schools of Writing Usul Fiqh After as-Syafi'i, many scholars began to compile books on ushul fiqh. Some summarized it, while others discussed it at length. Then two schools of thought emerged in writing ushul fiqh, the theological school (ahlu al-kalam) and the Hanafi school. Each uses a different method. From this background, the author sees that Imam Syafi'i had knowledge of the two schools of thought that differed, so he was indeed the right person to be the first to write a book on the science of ushul. In addition to Ar-Risalah, Imam Syafi'i also has other works on the science of ushul, such as: the book Jima'ul-ilmi, Ibthalul-istihsan, and Ikhtilaful-hadith. From this study, it was found that the rules of ushuliyah are guidelines or basic rules used to istinbath (take) sharia law from existing evidence. The goal is to achieve human welfare through the establishment of laws in accordance with sharia principles. The principles of Usuliyah are an important methodology in the science of ushul fiqh which functions to explore and establish sharia law from its sources, such as the Qur'an and Sunnah.